Sex-dependent neuro-deconvolution analysis of Alzheimer's disease brain transcriptomes according to CHI3L1 expression levels - Sanfilippo, Cristina; Castrogiovanni, Paola; Imbesi, Rosa; Musumeci, Giuseppe; Vecchio, Michele; Li Volti, Giovanni; Tibullo, Daniele; Broggi, Giuseppe; Caltabiano, Rosario; Ulivieri, Martina; Kazakova, Maria; Parenti, Rosalba; et al. (Journal of neuroimmunology, 2022)
Glial activation and related neuroinflammatory processes play a key role in the aging and progression of Alzheimer's disease (AD). CHI3L1/ YKL40 is a widely investigated chitinase in neurodegenerative diseases and recent studies have shown its involvement in aging and AD. Nevertheless, the biological function of CHI3L1 in AD is still unknown. Here, we collected microarray datasets from the National Center for Biotechnology Information (NCBI) brain samples of not demented healthy controls (NDHC) who died from causes not attributable to neurodegenerative disorders (n = 460), and of deceased patients suffering from Alzheimer's disease (AD) (n = 697). The NDHC and AD patients were stratified according to CHI3L1 expression levels as a cut-off. We identified two groups both males and females, subsequently used for our statistical comparisons: the high CHI3L1 expression group (HCEG) and the low CHI3L1 expression group (LCEG). Comparing HCEG to LCEG, we attained four signatures according to the sex of patients, in order to identify the healthy and AD brain cellular architecture, performing a genomic deconvolution analysis. We used neurological signatures (NS) belonging to six neurological cells populations and nine signatures that included the main physiological neurological processes. We discovered that, in the brains of NDHC the high expression levels of CHI3L1 were associated with astrocyte activation profile, while in AD males and females we showed an inflammatory profile microglia-mediated. The low CHI3L1 brain expression levels in NDHC and AD patients highlighted a neuronal activation profile. Furthermore, using drugs opposing CHI3L1 transcriptomic signatures, we found a specific drug profile for AD males and females characterized by high levels of CHI3L1 composed of fostamatinib, rucaparib, cephaeline, prednisolone, and dinoprostone. Brain levels of CHI3L1 in AD patients represent a biological signature that allows distinguishing between males and females and their likely cellular brain architecture. •Deconvolution method represents a new approach to define the brain cells' architecture AD.•CHI3L1 is a chitinase high modulated in neurodegenerative diseases and AD.•In AD brains the high expression levels of CHI3L1 were associated with an inflammatory profile.•Neuronal activation profile is significantly activated in AD patients with low CHI3L1 expression.•Anti-AD drugs identified by L1000FWD showed fostamatinib, rucaparib, cephaeline, prednisolone, and Dinoprostone.